Methods in bioengineering : organ preservation and reengineering - Uygun, Korkut; Lee, Charles Y. (Artech House, 2011)
Written and edited by recognized experts in the field, the new Artech House Methods in Bioengineering book series offers detailed guidance on authoritative methods for addressing specific bioengineering challenges. Offering a highly practical presentation of each topic, each book provides research engineers, scientists, and students with step-by-step procedures, clear examples, and effective ways to overcome problems that may be encountered. This first-of-its-kind volume addresses the important challenge of organ preservation and reengineering. The book presents cutting-edge techniques for damaged livers and hearts via normothermic perfusion, hypothermic machine perfusion for the liver, kidney and pancreas, and imaging techniques to assess the viability of injured kidneys. You also find methods to decellularize whole organs to create scaffolds for tissue engineering. Moreover, the book presents an approach to enhancing hepatocyte recovery from marginal livers. Publisher abstract.
Keywords: ORGAN; Preservation of organs, tissues, etc. -- Methodology.; Bioengineering -- Methodology.; elektronické knihy; electronic books